2011
DOI: 10.1088/1674-4527/11/9/004
|View full text |Cite
|
Sign up to set email alerts
|

Multiband fitting to three long GRBs with Fermi/LAT data: structured ejecta sweeping up a density-jump medium

Abstract: We present broadband (radio, optical, X-ray and GeV) fits to the afterglow light curves and spectra of three long-duration gamma-ray bursts (GRBs 080916C, 090902B, and 090926A) detected by the Gamma-Ray Burst Monitor (GBM) and Large Area Telescope (LAT) instruments on the Fermi satellite. Using the observed broadband data, we study the origin of the high energy emission, and suggest that the early-time GeV emission and the late-time radio, optical, and X-ray afterglows can be understood as being due to synchro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 71 publications
(138 reference statements)
1
9
0
Order By: Relevance
“…The posterior probability density functions for the physical parameters, i.e., E k,iso,on , Γ 0 , θ c , θ jet /θ c , θ v /θ c , p, ǫ e , ǫ B , A * , and R tr , are presented in Figure 8, where only the fitting result of GRB 120326A is shown as an example. The optimal result from MCMC fitting is shown in Figure 7 with blue line (XRT) and red line (optical), and the obtained parameters at the 1σ confidence level are reported in Table 1, where the values of the transition radius R tr (i.e., 1.05 × 10 17 cm, 6.31 × 10 16 cm, and 3.98 × 10 17 cm for GRBs 120326A, 120404A and 100814A, respectively) are consistent with those found in other bursts (e.g., Kong et al 2010;Feng & Dai 2011a;Ramirez-Ruiz et al 2001;Li et al 2020). It can be found that both the X-ray afterglow and the optical afterglow of these bumps can be well modelled with an off-axis observed external-forward shock in a free-to-shocked wind environment.…”
Section: Case Studysupporting
confidence: 83%
See 1 more Smart Citation
“…The posterior probability density functions for the physical parameters, i.e., E k,iso,on , Γ 0 , θ c , θ jet /θ c , θ v /θ c , p, ǫ e , ǫ B , A * , and R tr , are presented in Figure 8, where only the fitting result of GRB 120326A is shown as an example. The optimal result from MCMC fitting is shown in Figure 7 with blue line (XRT) and red line (optical), and the obtained parameters at the 1σ confidence level are reported in Table 1, where the values of the transition radius R tr (i.e., 1.05 × 10 17 cm, 6.31 × 10 16 cm, and 3.98 × 10 17 cm for GRBs 120326A, 120404A and 100814A, respectively) are consistent with those found in other bursts (e.g., Kong et al 2010;Feng & Dai 2011a;Ramirez-Ruiz et al 2001;Li et al 2020). It can be found that both the X-ray afterglow and the optical afterglow of these bumps can be well modelled with an off-axis observed external-forward shock in a free-to-shocked wind environment.…”
Section: Case Studysupporting
confidence: 83%
“…Please see Pe 'er & Wijers (2006) for details. Here, R tr , i.e., the free-wind boundary, is the transition radius from the free-wind to the shocked-wind (Kong et al 2010;Feng & Dai 2011a;Ramirez-Ruiz et al 2001) and depends on the age of the massive star wind and proper tracking of the shocked medium cooling. In summary, the mass density of the free-to-shocked wind circum-burst environment is described as…”
Section: Dynamics and Radiation Of The External-forward Shockmentioning
confidence: 99%
“…For the wind-ISM transition, this second power-law is shallower than the pre-transition index. Such a signature has been claimed in a number of GRBs: 030226 (Dai & Wu 2003), 081109A (Jin et al 2009), 080916C, 090902B, 090926A (Feng & Dai 2011) and 130907A (Veres et al 2015). While suggestive, none of these are conclusive; in some cases the supposed transition occurs in gaps between the data, and in others the light curve behaviour could be explained by the transition between the prompt emission tail and the rise of the underlying afterglow, or the passage of ν c through the X-ray bandpass.…”
Section: Environmentsmentioning
confidence: 83%
“…Dai & Lu 2002) should in theory be commonly observed within the LGRB afterglow population. However, despite several claims (Dai & Wu 2003;Jin et al 2009;Feng & Dai 2011;Veres et al 2015), such a signature has never been unambiguously identified.…”
Section: Introductionmentioning
confidence: 99%
“…(2) The long-term GeV emission may be originated from the external shock. This requires some extreme parameters for the external shock [322,323], a radiative blastwave [319] or a Klein-Nishina cooling dominated shock [325,326]. GeV emission during the prompt emission phase, however, is not easy to interpret within the external shock model [327,328,320], and is likely of an internal origin, as suggested by the data [155].…”
Section: Origin Of High Energy Emissionmentioning
confidence: 99%